Safety and Efficacy of Camrelizumab in Combination With Nab-Paclitaxel Plus S-1 for the Treatment of Gastric Cancer With Serosal Invasion - Lin, Ju-Li; Lin, Jian-Xian; Lin, Jun Peng; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; Wang, Jia-bin; Lu, Jun; Chen, Qi-Yue; Huang, Chang-Ming (Frontiers in Immunology, 2022)
Objective To investigate the safety and efficacy of camrelizumab in combination with nab-paclitaxel plus S-1 for the treatment of gastric cancer with serosal invasion. Method Two hundred patients with gastric cancer with serosal invasion who received neoadjuvant therapy from January 2012 to December 2020 were retrospectively analyzed. According to the different neoadjuvant therapy regimens, the patients were divided into the following three groups: the SOX group (S-1 + oxaliplatin) (72 patients), SAP group (S-1 + nab-paclitaxel) (95 patients) and C-SAP group (camrelizumab + S-1 + nab-paclitaxel) (33 patients). Result The pathological response (TRG 1a/1b) in the C-SAP group (39.4%) was not significantly different from that in the SAP group (26.3%) and was significantly higher than that in the SOX group (18.1%). The rate of ypT0 in the C-SAP group (24.2%) was higher than that in the SAP group (6.3%) and the SOX group (5.6%). The rate of ypN0 in the C-SAP group (66.7%) was also higher than that in the SAP group (38.9%) and the SOX group (36.1%). The rate of pCR in the C-SAP group (21.2%) was higher than that in the SAP group (5.3%) and the SOX group (2.8%). The use of an anti-PD-1 monoclonal antibody was an independent protective factor for TRG grade (1a/1b). The use of camrelizumab did not increase postoperative complications or the adverse effects of neoadjuvant therapy. Conclusion Camrelizumab combined with nab-paclitaxel plus S-1 could significantly improve the rate of tumor regression grade (TRG 1a/1b) and the rate of pCR in gastric cancer with serosal invasion.